Tip 2 diyabetli hastalara ayak bakım becerisinin kazandırılması - Kaymaz, Döndü Koçak (My University, 2005)
Araştırma; en az bir yıl önce WHO kriterlerine göre Tip 2 diyabet tanısı almış, 40 yaş ve üzeri diyabetlilere ayak bakım becerisinin kazandırılması amacıyla müdahale araştırması olarak planlandı.Çalışma 01.11.2003 - 01.11.2004 tarihleri arasında SB. Şişli Etfal Eğitim ve Araştırma Hastanesi Dahiliye Endokrinoloji Polikliniğ'ine başvuran 37 diyabetli hasta ile gerçekleştirildi. Araştırmanın ilk 3 aylık döneminde, araştırmacı tarafından materyal ve içerik oluşturuldu. Hastalarla ilk görüşmeden 3'er ay sonra 2 kez kontrole çağrılarak toplam 3 kez görüşüldü. Ayak bakımıyla ilgili eğitim verilerek ayak muayeneleri yapıldı.Diyabetlilerin sosyo-demografik özellikleri ve ayak bakım alışkanlıklarını belirleyen 36 sorudan oluşan hasta tanılama formu, Diyabet Hemşireliği Derneği tarafından oluşturulan ayağın ısı, hidrasyon, ödem, renk, nabız, tırnak kesimi, parmak arası muayenesi, pençe parmak, duyu kaybı, kas gücü ve deformite durumunu belirleyen ayak değerlendirme formu, hastaların ayak bakım alışkanlıklarını belirleyen 20 sorudan oluşan ayak bakım alışkanlığını değerlendirme formu ile laboratuvar bulguları, boyu, kilosu, beden kitle indeksinin kaydedildiği metabolik konrol değişkenleri formu ile veriler toplandı. Koruyucu duyu testi 5.07 Semmes-Weinstein monoflament kullanılarak yapıldı. Olguların %62.6'sını kadınlar oluşturdu. Diyabetlilerin %35.1'i 40-50 yaş arasındaydı. Grubun %83.8'i evliydi. Grubun öğrenim durumları ve ekonomik durumları düşüktü. %51.4'ünü emekliler oluşturdu. Eğitim öncesi, eğitimden üç ay ve eğitimden altı ay sonraki ayak bakım alışkanlıkarında istatistiksel olarak anlamlı değişiklikler saptanırken ( p< 0.05 ), metabolik kontral değişkenlerinde ise anlamlı fark belirlenmedi ( p > 0.05 ). Diyabetlilere verilen düzenli eğitim ve muayene ile diyabetlilerin olumlu ayak bakım alışkanlığı kazanmasını sağlayarak geç dönemde oluşacak ayak komplikasyonlarının azalacağı düşünülmektedir. Bu nedenle hastalara hemşirelerin ve sağlık ekibinin düzenli olarak ayak bakımına yönelik eğitimleri vermesi ve ayak muayenelerini yapmaları önerilmektedir. yabet, diyabetik ayak, diyabet eğitimi, ayak muayenesi, ayak bakımı, 5.07 Semmes-Weistein Monoflament. TO BE ACQUIRED OF FOOT CARING SKILL TO THE TYPE II DIABETIC PATIENTS

This study was planned as an intervention study. The aim of this study is to be acquired of foot caring skill to the diabetics who are at least 40 years old, and got Type II Diabetes diagnose at least a year ago according to the WHO criteria's. This study was realized with 37 diabetic patients who applied to Şişli Etfal Hospital Internal Disease Department and Endocrinology Policlinics between the dates of 01.11.2003 and 01.11.2004, and is suitable to the criteria's that are determined. In the first three months of the research, the literatures were examined for preparing the programme and contents of the education and materials and contents were occurred by the researcher. Then the researcher had interviews with the patients for three times in three months distance. Every patient was talked one by one. And their foot caring habits were appraised. After the foot care education the patient foot examinations were done. In this study four kinds of forms were used for collecting data. First form is a patient diagnostic form which has 36 questions which are determining socio demographic properties and foot caring habits of diabetic patients. Second form is a foot evaluating form that was formed by Diabetes Nursing Society. This form determines heat, hydration, oedema, colour, pulse, fingernail cutting of foot and interval of fingers examination, the loss of sense, and the condition of muscle power and deformed of foot. Third form is a foot coring habits form that includes 20 questions. The last form is metabolic control variables form which is used to determine laboratory results, heights, weights and body mass indexes of the patients. And also in this study 5.07 Semmes Weinstein monofilament test was used for the preventive sense test. %62.6 of the participants is female. %35.1 of the diabetic patients ages are between 40-50 years old. %83.8 of people who participate to this study is married. Education level and economical status of the group are low. Retired peoples are percentage is %51.4. Statistically meaningful changes were found in the participants' foot caring habits between, before the education, after three months from the education and after six months from the education (p < 0.05). Statistically meaningful changes were not found in the metabolic control variables between before the education, after three months from the education and after six months from the education (p > 0.05). It is thought that diabetics have affirmative foot caring habits with regular education and examination and foot complications will be reduced in the latest period. So that, it is suggested that nurses and the other members of health team should give regular education about foot caring to patients and do foot examinations. Key words: Type 2 diabetes, diabetic foot, diabetes education, foot examination, foot care, 5.07 Semmes Weinstein Monofilament.
Keywords: Diyabet Hastaları; Hastalıklar; iç salgı yapıcı sistemler hastalıkları; Kan yapıcı; lenfatik; Şeker hastalığı (diabetes mellitus); Teknoloji (Uygulamalı bilimler); Tıp bilimleri